2000
DOI: 10.1063/1.1290046
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of narrow-band terahertz generation from periodically poled lithium niobate

Abstract: Femtosecond optical pulses are used to generate narrow-band terahertz wave forms via optical rectification in a periodically poled lithium niobate crystal. By cooling the crystal to reduce losses due to phonon absorption, we are able to obtain bandwidths as narrow as 18 GHz at a carrier frequency of 1.8 THz. Temperature-dependent measurements show insignificant bandwidth broadening between 10 and 120 K, although the terahertz power substantially decreases as the temperature increases. Absolute power measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…Recently, an alternative approach for the tunable narrow-band THz generation which had multi-cycles or arbitrary wave forms was demonstrated using a periodically poled nonlinear crystal [5][6]. For the generation of multi-cycles of THz waves the main idea was to use the group velocity mismatch between the optical and THz waves in the periodically poled structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an alternative approach for the tunable narrow-band THz generation which had multi-cycles or arbitrary wave forms was demonstrated using a periodically poled nonlinear crystal [5][6]. For the generation of multi-cycles of THz waves the main idea was to use the group velocity mismatch between the optical and THz waves in the periodically poled structure.…”
Section: Introductionmentioning
confidence: 99%
“…13 In 2000, Lee et al demonstrated that a narrow-band THz radiation was obtained via optical rectification in periodically poled LiNbO 3 (PPLN) crystals, where the domain length is matched to the walk-off length between the optical and THz pulses. 7 The advantages of PPLN for the generation of THz are its abilities to simplify the optical scheme, to enlarge the tunability of THz spectrum and to obtain narrower bandwidths.…”
Section: Introductionmentioning
confidence: 99%
“…The later method can be used to generate broad-band, single-cycle THz waves under phase matching condition, 5,6 as well as to generate narrow-band, multicycle THz waves under quasi-phase matching condition. 7,8 As a femtosecond pulse illuminates a nonlinear crystal such as LiNbO 3 , ZnTe etc., a THz nonlinear polarization is generated via optical rectification. The ultrashort-pulse induced nonlinear polarization follows the intensity profile I(t) of the pulse.…”
Section: Introductionmentioning
confidence: 99%
“…The narrow-band THz seed pulses are generated by optical rectification of femtosecond laser pulse in a periodically poled lithium niobate (PPLN) crystal. 22,23 Although broad-band THz radiation can be generated in non-poled lithium niobate, 24 there is a large mismatch between the THz phase velocity and the group velocity of the 800 nm femtosecond laser pulses. This prevents efficient THz generation in a collinear geometry.…”
mentioning
confidence: 99%
“…The frequency of the forward (backward) generated wave is inversely proportional to the difference (sum) of the THz and optical group indices. 22,23 The PPLN crystal has multiple periodically poled regions with periodicities ranging from 18.50 to 20.90 lmin increments of 0.30 lm. The dimensions of the PPLN crystal are 5 Â 10 Â 0.5 mm and the dimension of each periodically poled region of the PPLN crystal is 5 Â 0.5 Â 0.5 mm.…”
mentioning
confidence: 99%